A successful retrieval of stripped outer coating of J-tip diagnostic guidewire from the left popliteal artery during elective coronary angiography - Damjanović, Miodrag; Šalinger-Martinović, Sonja; Djordjević-Radojković, Danijela; Koraćević, Goran; Miloradović, Vladimir (Vojnosanitetski pregled, 2014)
Introduction. Entrapment and fracture of diagnostic or therapeutic devices within the coronary circulatory system are a rare, but increasing problem. Case report. A 70-year-old man was admitted in our clinic for coronary angiography before the planned aortic valve replacement. An arterial sheath was inserted in the right common femoral artery. After introducing a J-tip diagnostic coronary guidewire into the aorta and advancing a left Judkins diagnostic catheter over it, suddenly occured peeling off of the wire´s hydrophilic coating at the aortic arch level. Very soon, this outer coating of guidewire carried by the blood stream was entered into the left femoral artery, then into the left popliteal artery. This stripped part of guidewire was successfully caught and extracted out by using a goose-neck snare catheter. Conclusion. A sudden stripping of outer coating of a J-tip diagnostic hydrophilic coronary guidewire during coronary angiography is possible to manage quickly and successfully by the use of a simple cathether.